Innovative Polymeric Biomaterials for Intraocular Lenses in Cataract Surgery - Kevin Y. Wu; Rebecca Khammar; Hafsah Sheikh; Michael Marchand (Journal of Functional Biomaterials)
Intraocular lenses (IOLs) play a pivotal role in restoring vision following cataract surgery. The evolution of polymeric biomaterials has been central to addressing challenges such as biocompatibility, optical clarity, mechanical stability, and resistance to opacification. This review explores essential requirements for IOL biomaterials, emphasizing their ability to mitigate complications like posterior capsule opacification (PCO) and dysphotopsias while maintaining long-term durability and visual quality. Traditional polymeric materials, including polymethyl methacrylate (PMMA), silicone, and acrylic polymers, are critically analyzed alongside cutting-edge innovations such as hydrogels, shape memory polymers, and light-adjustable lenses (LALs). Advances in polymer engineering have enabled these materials to achieve enhanced flexibility, transparency, and biocompatibility, driving their adoption in modern IOL design. Functionalization strategies, including surface modifications and drug-eluting designs, highlight advancements in preventing inflammation, infection, and other complications. The incorporation of UV-blocking and blue-light-filtering agents is also examined for their potential in reducing retinal damage. Furthermore, emerging technologies like nanotechnology and smart polymer-based biomaterials offer promising avenues for personalized, biocompatible IOLs with enhanced performance. Clinical outcomes, including visual acuity, contrast sensitivity, and patient satisfaction, are evaluated to provide an understanding of the current advancements and limitations in IOL development. We also discuss the current challenges and future directions, underscoring the need for cost-effective, innovative polymer-based solutions to optimize surgical outcomes and improve patients’ quality of life.